양측 폐문 림프절 종대를 동반한 간질성 결절성 폐침윤 - 윤재호; 여창동; 신은중; 송소향; 김치홍; 문화식; 송정섭; 박성학; Yoon, Jae Ho; Yeo, Chang Dong; Shin, Eun Joong; Song, So Hyang; et al. (Tuberculosis and respiratory diseases, 2006)
Lymphocytic interstitial pneumonia(LIP) is an uncommon condition in which the alveolar septa and extra-alveolar interstitial space are markedly expanded by small lymphocytes, plasma cells and histiocytes. Chest radiographs generally show nonspecific patterns with the most common pattern showing bibasilar reticular or reticulonodular infiltrates. Hilar or mediastinal lymphadenopathy and pleural effusions are usually absent. We encountered a 42-year-old female patient who was admitted to hospital because of exertional dyspnea and palpitation. The chest X-ray showed an enlarged bilateral hilar shadow and diffusely increased bronchovascular markings in both lung fields. The chest CT showed diffuse nodular infiltrations with mild septal thickening and combined patchy ground glass opacity in both lungs, and conglomerated mediastinal and bilateral hilar lymphadenopathy. A diagnosis of LIP was made from the tissue pathology taken by a thoracoscopic lung biopsy. The patient showed clinical and radiographic improvement after 3 months of treatment with prednisolone. We report a case of LIP presenting as diffuse nodular interstitial infiltrations with multiple mediastinal and bilateral hilar lymphadenopathy. 단순 흉부 X-선에서 양측성 폐문 림프절 비후를 보이는 대표적인 질환으로 유육종증, 림프종, 결핵, 폐암, 아밀로이드증, 브루셀라증, 콕시디오이데스진균증(Coccidioidomycosis) 등이 있다. LIP의 방사선학적 소견은 보통 비특징적이고, 초기 병변에서 양측 폐하에 망상, 망상결절성 침윤을 보이며 병이 진행됨에 따라 낭성 변화를 동반하고, 봉소상을 보이는 경우가 있으나, 본 증례의 환자와 같이 종격동과 양측 폐문에 림프절 종대를 동반하는 경우에 대한 보고는 흔치 않다. 저자들은 흉부 X-선 및 CT상 종격동과 양측 폐문부의 림프절 종대를 동반한 간질성 결절성 폐침윤 소견을 나타낸 환자에서 흉강경하 폐 생검을 통해 진단된 LIP를 경험하였기에 문헌고찰과 함께 보고하는 바이다.